2018
DOI: 10.1186/s13104-018-3581-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of resistance genes encoding ESBLs in Enterobacteriaceae isolated from biological samples in health centers in Ouagadougou, Burkina Faso

Abstract: ObjectiveResistance to antibiotics most especially third generation cephalosporins has assumed a worrisome dimension globally. Genes conferring these resistance which are mediated by enzymes known as extended spectrum beta-lactamases (ESBLs) are now wide spread among several Enterobacteriaceae species. However there is paucity of data regarding the distribution of these genes in Burkina Faso. Hence this prospective study aims to determine the prevalence and distribution of ESBL encoding genes in ESBL producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 25 publications
6
22
7
1
Order By: Relevance
“…In the majority of the surveys, blaCTX-M-15 was the most common ESBL gene detected worlwide in animals and humans. [12,28,29] This result has been also found in Burkina Faso among human clinical samples and fecal carriage [30,31,32]. Then E. coli strains belonged majoritary to phylogroup A in our study.…”
Section: Discussionsupporting
confidence: 80%
“…In the majority of the surveys, blaCTX-M-15 was the most common ESBL gene detected worlwide in animals and humans. [12,28,29] This result has been also found in Burkina Faso among human clinical samples and fecal carriage [30,31,32]. Then E. coli strains belonged majoritary to phylogroup A in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Our study showed that all the E. coli isolates (5/5) were ESBL producers in agreement with 95.60% reported in Togo [41]. The presence of ESBL-producing bacteria in hospitals is a major challenge that affects both developed and developing countries [26]. It is known that β-Lactams (mainly extended-past spectrum cephalosporins and carbapenems) and uoroquinolones constitute the main therapeutic choices to treat infections caused by Enterobacteriaceae.…”
Section: Discussionsupporting
confidence: 86%
“…The present study showed that the bla OXA genes were the most common ß-lactamase-producing genes (57.14%), followed by bla CTX-M (7.14%). These ndings contrast with those previously reported in Burkina Faso [8,26]. Otherwise, a spread of bla CTX-M , particularly CTX-M-15 in community and hospital settings has been reported [32,46,47].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The enzymatic degradation of beta-lactam ring by beta-lactamases is the most effective resistance mechanism that bacteria have for the fight back the antibacterial effect of betalactam antibiotics [8]. The genes encoding the beta-lactamases have been widespread between different bacterial populations, mainly due to mobile genetic elements such as carrier plasmids and transposons.…”
Section: Introductionmentioning
confidence: 99%